2018
DOI: 10.2147/amep.s142605
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheterization training: current perspectives on the role of simulation

Abstract: Simulation is a popular and effective training modality in medical education across a variety of domains. Central venous catheterization (CVC) is commonly undertaken by trainees, and carries significant risk for patient harm when carried out incorrectly. Multiple studies have evaluated the efficacy of simulation-based training programs, in comparison with traditional training modalities, on learner and patient outcomes. In this review, we discuss relevant adult learning principles that support simulation-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 77 publications
1
24
1
Order By: Relevance
“…21 Soffler et al reviewed the literature on simulation-based central venous catheterization training and highlighted its use at a variety of institutions. 22 The review article discusses how we can translate simulation-based training into practice. They highlight the model proposed by Alsaad et al which divided the curriculum into four training sections beginning with a 30-minute review of anatomy, followed by a 30-minute review of sterile technique and universal precautions, a 45-minute training session on US use, and finally a 45-minute hands-on practical station.…”
Section: Training Modelsmentioning
confidence: 99%
“…21 Soffler et al reviewed the literature on simulation-based central venous catheterization training and highlighted its use at a variety of institutions. 22 The review article discusses how we can translate simulation-based training into practice. They highlight the model proposed by Alsaad et al which divided the curriculum into four training sections beginning with a 30-minute review of anatomy, followed by a 30-minute review of sterile technique and universal precautions, a 45-minute training session on US use, and finally a 45-minute hands-on practical station.…”
Section: Training Modelsmentioning
confidence: 99%
“…Simulation based mastery learning (SBML), increasingly utilized in a variety of contexts including for procedural and clinical skills, improves knowledge and skill . Notably, several studies have shown that physician experience does not correlate with performance level in a controlled setting and that SBML improves performance regardless of prior experience …”
Section: Failing To Use Us Guidance For All Nthc Insertionsmentioning
confidence: 99%
“…Central Venous Access (CVA) is one of the most common invasive procedures at the Intensive Care Unit [ 1 ]. It is prescribed to administer vasoactive drugs, infuse medication, do hemodialysis or hemofiltration and cardiac pacemaking, among other indications [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is prescribed to administer vasoactive drugs, infuse medication, do hemodialysis or hemofiltration and cardiac pacemaking, among other indications [ 2 ]. The most common accesses for these procedures are the subclavian vein, internal jugular vein, and femoral vein [ 1 ]. There are two main methods to localize the vein that needs to be punctured: anatomical landmarks and ultrasound (US).…”
Section: Introductionmentioning
confidence: 99%